Geometric approaches to input file modification for part quality improvement in additive manufacturing. (October 2015) - Zha, Wentao; Anand, Sam
Abstract: Additive manufacturing (AM) machines use the Stereolithography (STL) file as standard input file format to build parts. STL model is a triangular faceted approximation of a CAD model, which represents a part with less accuracy than the CAD model. Commercial softwares have the ability to convert a CAD file into an STL file based on a user defined threshold value to uniformly convert the entire part body into triangular facets. Increasing the geometric accuracy of STL models is typically accomplished by decreasing the user defined threshold value, which results in an increase in STL file size. In this research, a Surface-based Modification Algorithm (SMA) that adaptively and locally increases the facet density of an STL model is presented. The Surface-based Modification Algorithm is an error minimization approach to modify the STL facets locally based on chordal error, cusp height and cylindricity error for cylindrical features and is typically able to achieve a smaller file size compared to uniform export option. A novel bounding box based algorithm is developed to calculate cusp height error from the point cloud generated from the part by slicing the STL facets or from the CAD surface. Final results show a distinct improvement in the part error of the STL model using Surface-based Modification Algorithm (SMA) when compared to the original STL file.